2005
DOI: 10.1159/000086988
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Is Associated with an Increased Female Colorectal Cancer Risk: A Nested Case-Control Study in Japan

Abstract: Objective: To elucidate whether leptin is involved in the etiology of female colorectal cancer. Methods: A case-control study nested in the Japan Collaborative Cohort Study. We compared serum leptin levels in 58 cases of female colorectal cancer with those in 145 controls matched for study area and age. Data were analyzed using a conditional logistic regression model with adjustments for known risk factors for the development of colorectal cancer. Quintile cutoff points were determined on the distribution of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 53 publications
(37 reference statements)
5
61
1
6
Order By: Relevance
“…A positive positive association between pre-diagnostic circulating leptin concentrations and risk of colon cancer in men was also observed in a study from Norway [73]. A higher risk of colorectal cancer in women with high prediagnostic leptin concentrations was oberved in the Japan Collaborative Cohort Study [74] and in the Women's Health Initiative cohort [75]. In a meta-analysis including six prospective studies, higher leptin concentrations were significantly associated with higher risk of colorectal cancer [76].…”
Section: Leptinmentioning
confidence: 61%
“…A positive positive association between pre-diagnostic circulating leptin concentrations and risk of colon cancer in men was also observed in a study from Norway [73]. A higher risk of colorectal cancer in women with high prediagnostic leptin concentrations was oberved in the Japan Collaborative Cohort Study [74] and in the Women's Health Initiative cohort [75]. In a meta-analysis including six prospective studies, higher leptin concentrations were significantly associated with higher risk of colorectal cancer [76].…”
Section: Leptinmentioning
confidence: 61%
“…The association between leptin concentration and colorectal cancer was also evaluated in women, in a case-control study conducted in Japan, suggesting that leptin increases substantially the risk of female colorectal cancer, independent of BMI [52] .…”
Section: Leptinmentioning
confidence: 99%
“…(2012) found association between the level of leptin and progression of CRC in postmenopausal women and documented that the effect of hyperleptinemia was mediated mostly by insulin. Tamakoshi et al (2005) reported that invasiveness of CRC in women is associated with a high level of leptin in serum. It is suggested that only very high levels of leptin and other metabolic factors acting simultaneously (levels of C-peptide, HbA1c, and leptin/ObR ratio) activate and increase CRC proliferation (Stocks et al, 2008).…”
Section: Obesity-leptin and Adiponectinmentioning
confidence: 99%